Overall Thermal Transfer Value (OTTV) Analysis of the Banten Provincial Language Office Building - Moh. Asep Somantri Somantri; Annisa Marwati (RUSTIC, 2026)
This study evaluates the thermal performance of the building envelope at the Banten Provincial Language Office through an analysis of the Overall Thermal Transfer Value (OTTV). The objective of this study is to calculate the OTTV value and identify the facade elements that contribute the greatest heat load to ensure compliance with the SNI 03-6389-2020 standard (maximum 35 W/m²). The primary method used was a mixed-methods approach employing a case study methodology, which involved field observations, analysis of construction drawings, and an OTTV spreadsheet calculator provided by the Ministry of Public Works and People’s Housing (PUPR). The main results show that the current OTTV value is 69.43 W/m², which does not meet the national standard. The east facade contributes the highest heat gain (85.10 W/m²) due to a window-to-wall ratio (WWR) of 54.72% and 8 mm-thick clear glass. Building orientation, materials, glass type, opening area (WWR), and the use of shading systems are critical factors in calculating the OTTV value. Modifying the glass material by using Stopray Double Glass on the east and north facades successfully reduced the total OTTV value by 50.02% to 34.70 W/m². This material intervention proved effective in meeting national energy conservation standards.